P-GaN Contact Study by Means of Electrochemical Short Loop. (1st December 2022) - Suman, Sidharth; Martin, Brigitte; Dupre, Ludovic; Rol, Fabien; Templier, Roselyne; Martinez, Eugenie; Sadki, Said; Pernel, Carole
Abstract : Surface states and contamination affects the efficiency of Gallium Nitride (GaN) based devices such as HEMTs, LEDs, photodetectors etc. In this work, several wet chemical treatment has been performed for the surface treatment of p-GaN, in order to achieve low-resistance ohmic contacts. The effect of surface treatment is observed by studying the flatband potential across the p-GaN/electrolyte interface via, electrochemical characterization. The electrochemical method of "Mott-Schottky characterization" gives simple and quick way of analysing the effect of different treatments, without the need of device fabrication. The effect of surface treatment are further investigated via, X-ray Photoelectron Spectroscopy and Atomic Force Microscopy. The potential surface treatments from experimental findings are integrated into device processing steps in order to realize effect of surface treatment on the p-GaN/metal contacts. The electrochemical characterization shows that HCl results in least flatband potential. Further, The electrical test shows that HCl treatment results in significant orders of magnitude improvement in contact resistance and electrical performance of the devices. This shows that short loop electrochemical characterization can be used for predicting surface treatment in order to improve electrical characteristics of the device.